Alternative polyadenylation diversifies post‐transcriptional regulation by selective RNA–protein interactions. Issue 2 (25th February 2014) - Gupta, Ishaan; Clauder‐Münster, Sandra; Klaus, Bernd; Järvelin, Aino I; Aiyar, Raeka S; Benes, Vladimir; Wilkening, Stefan; Huber, Wolfgang; Pelechano, Vicent; Steinmetz, Lars M
Synopsis <boxed-text content-type="graphic" id="msb135068-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> A single gene can give rise to many isoforms via alternative polyadenylation. This study demonstrates that isoforms of each gene can have different molecular phenotypes like RNA stability and interaction with proteins, diversifying the functional potential of the genome. Divergent post‐transcriptional fates of 3′ transcript isoforms are revealed at a genome‐wide level. New techniques are presented that accurately measure isoform‐specific stability and protein binding, thus demonstrating widespread variation in both. Even variations of a few nucleotides are associated with variations in transcript stability. Transcript binding to PUF3 and subsequent destabilization occurs in an isoform‐specific manner.